Zoomland: exploring scale in digital history and humanities - Armaselu, Florentina; Fickers, Andreas (Studies in digital history and hermeneutics, 2024)
Despite a variety of theoretical and practical undertakings, there is no coherent understanding of the concept of scale in digital history and humanities, and its potential is largely unexplored. A clearer picture of the whole spectrum is needed, from large to small, distant to close, global to local, general to specific, macro to micro, and the in-between levels.